Transistorgelykstroomversterkers en die temperatuurstabilisasie daarvan - Verster, T. C.(Theunis Christiaan) (Stellenbosch : Stellenbosch University, 2012)
Verhandeling (M. Ing.) -- Universiteit van Stellenbosch, 1959.